Maternal ethnicity and risk of neural tube defects: a population-based study - Ray, Joel G. (Canadian Medical Association, 2004)
BACKGROUND: Maternal body mass and the presence of diabetes mellitus are probable risk factors for neural tube defects (NTDs). The association between maternal ethnicity and the risk of NTDs remains poorly understood, however. METHODS: We performed a retrospective population-based study and included all women in Ontario who underwent antenatal maternal screening (MSS) at 15 to 20 weeks' gestation between 1994 and late 2000. Self-declared maternal date of birth, ethnicity and weight and the presence of pregestational diabetes mellitus were recorded in a standardized fashion on the MSS requisition sheet. NTDs were detected antenatally by ultrasonography or fetal autopsy and postnatally by considering all live and stillborn affected infants beyond 20 weeks' gestation. The risk of open NTD was evaluated across the 5 broad ethnic groups used for MSS, with white ethnicity as the referent. RESULTS: Compared with white women (n = 290 799), women of First Nations origin (n = 1551) were at increased associated risk of an NTD-affected pregnancy (adjusted odds ratio [OR] 5.2, 95% confidence interval [CI] 2.1–12.9). Women of other ethnic origins were not at increased associated risk compared with white women (women of Asian origin [n = 75 590]: adjusted OR 0.9, 95% CI 0.6–1.3; black women [n = 25 966]: adjusted OR 0.6, 95% CI 0.3–1.1; women of “other” ethnic origin [n = 10 009]: adjusted OR 0.1, 95% CI 0.02–0.9). INTERPRETATION: The associated risk of NTD-affected pregnancies was higher among women of First Nations origin than among women of other ethnic origins. The mechanisms for this discrepancy should be explored.